Maqasidi Leadership of Minority Religions Figure for Maintaining Tolerance in Manado, Indonesia - Ismail, Feiby; Arifin, Zainal; Rahmi, Sri (Jurnal Pendidikan Islam, 2020)
Manado's Muslim minority mindset stops social, political, and religious activities. Although Islam is the second-largest religion after Protestantism, this mindset can be seen by the impression that Manado is a 'Christian City' known as the “Tower of a Thousand Churches.” This article describes the strategy of minority religious leaders (Islam) in tolerating the perspective of Maqasid al-Syari'ah. The research data was collected through observation and in-depth interviews with religious leaders from the Islamic boarding school Kiai, IAIN Manado lecturers, and Muslim youth. The research findings show that first, the values ​​of religious tolerance in Manado have developed in the form of slogans, such as "Torang Samua Basudara," " Torang Samua Ciptaan Tuhan, "and "Si Tou Timou Tumou Tou," second, the strategy of Islamic religious leaders in maintaining tolerance through (1) mutual respect for beliefs, (2) fighting for religious teachers and places of worship (mushola) in public schools, (3) creating dialogue forums between religious communities, (4) enlivening Islamic syi'ar, such as majlis taklim, the graduation ceremony for students from all over North Sulawesi, and (5) halal certification. This finding has implications for the Maqasidi type for religious minority leaders in tolerance to protect Muslims' faith.